Blender beginner's bootcamp. (Packt Publishing, 2023)
Blender is a free and open-source 3D creation software for various applications, including video game assets, film production, and animations. It offers a variety of tools and techniques, making it versatile software for 3D modeling and animation. The course begins with essential 3D modeling fundamentals and gradually advances to physically based rendering (PBR) textures using a free material pack. The course covers modeling intricate vehicles and sci-fi props, building unique houses with personalized elements, creating traditional parts for fantasy settings, enhancing environments with realistic foliage, using physics simulations to populate scenes, and designing structurally sound bridges and boats for aquatic settings. You can confidently transform 2D logos into 3D projects, create realistic textures, materials, and lighting to add depth and realism to your models and use Blender's new interface and shortcuts. Video lessons and access to a download pack with Blender files, materials, textures, and reference silhouettes accompany each project. By the end of the course, you will be equipped with the necessary knowledge and skills to create stunning 3D projects in Blender. This course will give you a solid foundation and the confidence to tackle 3D modeling head-on. What You Will Learn Familiarize yourself with Blender's interface and fundamental tools Create stunning 3D models for games and virtual experiences Enhance environment design with realistic textures and materials Efficiently optimize and export models for different platforms Use advanced techniques such as sculpting and particle systems Develop professional workflow and gain valuable industry insights Audiuence This course is ideal for beginner to advanced 3D modelers, Blender enthusiasts, or artists looking to enhance their skills in environmental design. Whether you are interested in creating themed projects or specializing in game design, this course offers valuable knowledge and practical experience in asset creation using Blender. Ideal for students and those eager to stay updated with Blender's latest features. Prerequisites include a computer and Blender software (version 2.8 or above), a genuine interest in 3D modeling/environment design, and course resources, including a complete .blend file. About The Author 3D Tudor Limited By Neil Ian Bettison: Neil Bettison is a professional 3D artist with nine years of modelling experience, including assets, characters, and environments. After attending the University for Creative Arts (UCA) for a BA (Hons) Computer Games Arts degree, Neil began freelancing. In 2019, Neil Bettison founded 3D Tudor, a YouTube channel, to help other game developers because of his passion for 3D modeling. Neil is an excellent tutor known for his concise instructions and expertise in Blender, Unreal Engine 5, and Unity. His to-the-point guidance and years of experience make him a valuable resource for learning particle effects, complex asset animation, and game development.